2011
DOI: 10.4067/s0718-58392011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Sensory and Phenolic Characterization of ‘Elegant Lady’ and ‘Carson’ Peaches

Abstract: High quality fruits are increasingly demanded along with the need to ensure this attribute to consumers. Thus, this study was aimed at characterizing a melting ('Elegant Lady') and a non-melting flesh ('Carson') peach (Prunus persica (L.) Batsch) varieties by considering both their bioactive compound contribution and their sensory quality in ripe fruit at harvest and after a prolonged period of cold storage. Cultivars were evaluated at harvest (F0) and after 30 d of cold storage (F30), as well as after a matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…Its isomer, neochlorogenic acid, was also clearly detected. Both compounds are characteristic of peaches . This was consistent with the results obtained by Scattino et al and Tomás‐Barberán et al in other peach and nectarine cultivars.…”
Section: Discussionsupporting
confidence: 92%
“…Its isomer, neochlorogenic acid, was also clearly detected. Both compounds are characteristic of peaches . This was consistent with the results obtained by Scattino et al and Tomás‐Barberán et al in other peach and nectarine cultivars.…”
Section: Discussionsupporting
confidence: 92%
“…1), an isomer of chlorogenic acid, is a natural polyphenolic compound found in some types of dried fruits and a variety of other plant sources such as peaches [11]. Previous studies have shown that phenolic acids have outstanding antioxidant, antibacterial, antiviral, and antipyretic activities [12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…It also contains phenolic compounds such as catequins and leucoanthocyanins (19). The major phenolic compounds identified in peach are chlorogenic acid, catechins and epicatechins, with other compounds, including gallic acid, ellagic acid, rutin and isoquercetin (primary flavonols), cyanidin glucosides (anthocyanins) and malvin glycosides (20)(21)(22)(23). The presence of carotenoids such as β-cryptoxantine, β-carotene and α-carotene has been detected in peach fruit together with zeaxanthine, lycopene and xanthophyll.…”
Section: Introductionmentioning
confidence: 99%